OPTIMIZATION OF DIGITAL MARKETING IN INCREASING SALES AT ROEMAH RADJOET RISANTI DEPOK - Hamzah, Zeze Zakaria; Ilyas, Yasnimar; Anwar, Syaiful; Hamdani, Muchamad; Dwi Nugraha, Galih (LPPM Univ. Ibn Khaldun Bogor, 2023)
Background: Digital marketing is a way to increase sales. Digital marketing in Micro, Small, and Medium Enterprises has not been maximized. UMKM Roemah Radjoet still uses conventional marketing. Objective: Increase students' understanding of marketing and help increase sales. Method: Carry out digital marketing training and video creation. Results: Implementation of collaborative activities between Dewantara Institute of Economics Students, Depok Sejahtera High School Students, Dewantara Vocational High School Digital Marketing Coach, and Mulia Padjadjaran Hospital. All teams make videos of owners and knitted products, then upload them on social media. Conclusion: After uploading the video, it is hoped that it will further increase knowledge and increase knitted sales.